The DNA-Binding and Bioactivity of Rare Earth Metal Complexes - Yang, Li; Wang, Bochu; Tan, Jun; Zhu, Liancai (Mini Reviews in Medicinal Chemistry, 2013)
Recently more and more attention is paid to the rare earth metal complexes, because the properties of the rare earth metals are similar to those of the transition metals such as the similar atomic and the ionic radius. A large number of rare metal complexes were synthesized, and their bioactivities were also studied. This review highlights recent researches on the interaction of some rare earth metal complexes with DNA, analyzes how the configuration of the complexes influences the binding affinity, and focuses on the pharmacological activities of the complexes, such as anticancer, antibacterial, antioxidant, anti-inflammatory and anti-virus.
Keywords: DNA-binding